Scientific and methodological support in Paralympic sports - Vorobev, S. A.; Baryaev, A. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to improve the content of the system of scientific and methodological support for Paralympic sports, taking into account the results of application practice.